Economical Models for Reconfigurable Manufacturing Systems - BRUCCOLERI, Manfredi; PERRONE, Giovanni (Springer Link, 2006)
Dedicated manufacturing lines (DML), flexible manufacturing systems (FMS) and reconfigurable manufacturing systems (RMS) are, nowadays, the three production paradigms representing three ways of thinking and implementing production systems. Nevertheless, very few researches aim at clearly defining the convenience of such three manufacturing paradigms with regards to the market and competition characteristics in which the company plans to play. This chapter goes toward such a direction; in particular, an investment model for each kind of manufacturing system (DML, FMS, RMS) is proposed; these models are able to consider several market and competition issues such as product demand dynamic over the investment period, the possibility of several production mix composition, products direct costs and prices and so forth. The comparison of the manufacturing system configurations coming out from the optimization of the proposed models, allows to build up a general understanding about the field of economic convenience of each manufacturing system typology.